Effectiveness of Using Indonesian Language in the Learning Process at the Lombok Business Academy - Damayanti, Sri (Jurnal Ilmiah Mandala Education (JIME), 2024)
This research is motivated by the influence of the Indonesian language in the world of education in delivering the learning process at Lombok Business Academy lectures. The problems in this research are: 1) what is the role of Indonesian language in the world of education? 2) Can using Indonesian language help the learning process in delivering foreign language courses (English) and Financial Management courses? This research aims to examine the use of Indonesian language in learning at the Lombok Business Academy located in North Lombok, West Nusa Tenggara. The research method used is a qualitative research method. The research instrument used by researchers was interviews. Research object 2 (two) Lecturers and research locations at the Lombok Business Academy. The results of the research show that Indonesian language is dominantly used in speech events, because the language of instruction in learning is Indonesian language. In this way, the role in the world of education has a very important influence in the world of education which we should apply as a language of instruction in implementing the learning process for English language courses and Financial Management courses.